Dual-source evaporation of silver bismuth iodide films for planar junction solar cells. Issue 5 (10th January 2019) - Khazaee, Maryam; Sardashti, Kasra; Chung, Ching-Chang; Sun, Jon-Paul; Zhou, Hanhan; Bergmann, Eric; Dunlap-Shohl, Wiley A.; Han, Qiwei; Hill, Ian G.; Jones, Jacob L.; Lupascu, Doru C.; Mitzi, David B.
Abstract : Dual-source evaporation approach is applied to deposit AgBi2 I7, AgBiI4 and Ag2 BiI5 films; a planar junction AgBiI4 -solar cell is demonstrated. Abstract : Non-toxic and air-stable silver bismuth iodide semiconductors are promising light absorber candidates for photovoltaic applications owing to a suitable band gap for multi- or single-junction solar cells. Recently, solution-based film fabrication approaches for several silver bismuth iodide stoichiometries have been investigated. The current work reports on a facile and reproducible two-step coevaporation/annealing approach to deposit compact and pinhole-free films of AgBi2 I7, AgBiI4 and Ag2 BiI5 . X-ray diffraction (XRD) in combination with scanning electron microscopy (SEM)/energy-dispersive X-ray spectroscopy (EDX) analysis reveals formation of pure cubic ( Fd 3̄ m ) phase AgBi2 I7, cubic ( Fd 3̄ m ) or rhombohedra ( R 3̄ m ) phase AgBiI4, each with >3 μm average grain size, or the rhombohedral phase ( R 3̄ m ) Ag2 BiI5 with >200 nm average grain size. A phase transition from rhombohedral to cubic structure is investigated via temperature-dependent X-ray diffraction (TD-XRD). Planar-junction photovoltaic (PV) devices are prepared based on the coevaporated rhombohedral AgBiI4 films, with titanium dioxide (TiO2 ) and poly(3-hexylthiophene) (P3HT) as electron- and hole-transport layers, respectively. The best-performing device exhibited a power conversion efficiency (PCE) of as high as 0.9% with open-circuit voltage ( V OC ) > 0.8 V in the reverse scan direction (with significant hysteresis).